ANALYZING CHEMICAL KINETICS OF COAL GASIFICATION IN MINI GASIFIER REACTOR - M. Ade A. Efendi; Yenny Sofaety (Indonesian Mining Journal, 2016)
Coal gasification is a chemical reaction that has a purpose to change the original solid coal into gaseous compounds. Converting the coal into gaseous compounds will make the combustion process easier and results in increasing combustion efficiency. The sulfur and nitrogen are also easier to be separated in order to obtain cleaner flue gas. This paper presents kinetic analysis of coal gasification reactions in mini gasifier (or known as GasMin in Bahasa) reactor. The results show that the increase of the air-coal ratio (ACR) affected the maximum temperature of the reactor, which means that an increase of the intake air flow rate will increase the amount of oxygen for combustion reaction. Meanwhile, the increase of the team coal ratio (SCR) will increase flow rate of the mixture of air-steam feed. As a result, the ability of coal gasification has also increased. This will increase gasification efficiency around 3-5% which then will also increase the gas yield. The maximum value of SCR was 0.06, further than that of the yield gas and the q- value will slightly decrease. The simulation result showed that the producer gas was dominated by CO with 26.72% mole fraction; H2 with 14.06% mole fraction, and N2 with 47.88% mole fraction. Meanwhile CO2, CH4 and O2 mole fraction were 5%, 0.24%, and 1.20% respectively